2015
DOI: 10.1002/2015jc010716
|View full text |Cite
|
Sign up to set email alerts
|

A review of trend models applied to sea level data with reference to the “acceleration‐deceleration debate”

Abstract: Global sea levels have been rising through the past century and are projected to rise at an accelerated rate throughout the 21st century. This has motivated a number of authors to search for already existing accelerations in observations, which would be, if present, vital for coastal protection planning purposes. No scientific consensus has been reached yet as to how a possible acceleration could be separated from intrinsic climate variability in sea level records. This has led to an intensive debate on its ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 108 publications
(192 reference statements)
0
70
0
Order By: Relevance
“…It is acknowledged that some studies indicate uncertainties in the ability of EMD to detect long-term variations and acceleration in sea level [30,47], especially if the records are not long enough, though this problem is not unique to EMD and according to [33], it is not clear which of the many possible analysis methods is preferred for detection of sea level acceleration. Furthermore, a recent study [18] evaluated the statistics of ensemble EMD calculations using very long European sea level records and shows that for records long enough (even with some gaps) EMD can detect acceleration that is almost identical to that obtained by the standard least squares fitting methods.…”
Section: Emd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is acknowledged that some studies indicate uncertainties in the ability of EMD to detect long-term variations and acceleration in sea level [30,47], especially if the records are not long enough, though this problem is not unique to EMD and according to [33], it is not clear which of the many possible analysis methods is preferred for detection of sea level acceleration. Furthermore, a recent study [18] evaluated the statistics of ensemble EMD calculations using very long European sea level records and shows that for records long enough (even with some gaps) EMD can detect acceleration that is almost identical to that obtained by the standard least squares fitting methods.…”
Section: Emd Analysismentioning
confidence: 99%
“…As a result, the accelerations are estimated for the Bohai Sea (BS), Yellow Sea (YS), and East China Sea (ECS) separately. Visser et al [33] reviewed 30 trend models applied in the field of sea level research and concluded that varying trend approaches may lead to contradictory acceleration-deceleration inferences. Therefore, the present study compares three different methods, including the linear least squares fitting method, evolution of SLR rates method [20], and sea level rate difference method [29,34] to determine the SLA in the past 55-65 years over the China Seas.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding uncertainty is usually addressed by simulating the natural variability, represented by the residuals around the trend line, in Monte-Carlo experiments under the assumption that it follows a specific noise process (e.g., ref. 46). Although it has been widely accepted that an autoregressive process of the order 1 is suitable for this purpose (e.g., ref.…”
Section: Methodsmentioning
confidence: 99%
“…A number of different techniques have been used to estimate acceleration of local relative sea level (for example, see Visser et al [24]), but the results are controversial (see for example Kenigson and Han [25]; Piecuch and Ponte [26]). Haigh et al [27] demonstrated the difficulty of estimating accelerations from local tide-gauge observations, the necessity for long time series (Douglas [28] argued that almost 50 years was required), and the importance of removing unforced and naturally forced variability.…”
Section: Historical Sea Levelmentioning
confidence: 99%